Patient trying to tell something else: severe stress during COVID19 Pandemic - Abdullah, Fa’iza; Mohd Razib, Mohd Zhafri; Mat Nor, Mohd Basri (2021)
Identifying mental health illness poses a dilemma, particularly the distinction between heart disease and severe stress. Without early intervention, it can be escalating into psychiatric disorder and suicide.